Dork diaries I Love Paris - Russell, Rachel Renee; Russell, Erin; Russell, Nikki (New York SIMON SCHUSTER, 2023)
Join millions of Dork Diaries fans and discover if Nikki Maxwell and her friends (and frenemies) make it to Paris in the next instalment of the blockbuster series
English stories
For children aged 11 - 15 years
Keywords: English stories